La configuración del cristianismo como religión cósmica. El testimonio de San Juan Crisóstomo - González Blanco, A. (Antigüedad y Cristianismo, 1990)
Basing tiis study on tiie arguments used by Saint John Crisostom against those who refuted his expHcation of the Bible and of the criteria of the Christian way of life found therein, the author sets out to demonstrate how a new form of Christianism begins to take shape. Its principal characteristics can be conceived as those of a «cosmic religion» based in Nature (a form of Nature done by the faith - it's truth) but at the same time different, at least in dinamism, from the concept of the primitive Christianity, which remained alive up to the days when the Holy Bishop of Constantinople taught.